Prevalence of depression, anxiety in China during the COVID-19 pandemic: an updated systematic review and meta-analysis - Bin, Xiang; Qu, Ke-Yi; Wang, Yu-Hao; Chen, Li; Xiong, Yan-Jie; Wen, Jin Fu; Wei, Hua-Bo; Bing, Tan; Dan, Chun-Yan; Zhu, Jia-Quan (Frontiers in Public Health, 2024)
Background Mental health risks associated with the aftermath of the COVID-19 pandemic are often overlooked by the public. The aim of this study was to investigate the effects of the COVID-19 pandemic on depression and anxiety disorders in China. Methods Studies were analyzed and extracted in accordance with the PRISMA 2020 flowchart. The studies were screened and extracted using electronic databases including PubMed, Web of Science, Embase, Cochrane Library, and ClinicalTrials.gov according to the predefined eligibility criteria. The Cochrane Review Manager software 5.3.1 was used for data analysis and the risk of bias assessment. Results As of 2023, a total of 9,212,751 Chinese have been diagnosed with COVID-19 infection. A total of 913,036 participants in 44 studies were selected following the eligibility criteria, the statistical information of which was collected for meta-analysis. The pooled prevalence of depression and anxiety were 0.31 (95% CI: 0.28, 0.35; I2 = 100.0%, p < 0.001) and 0.29 (95% CI: 0.23, 0.36; I2 = 100.0%, p < 0.001), respectively. After performing a subgroup analysis, the prevalence of depression among women, healthcare workers, students, and adolescents was 0.31 (95% CI: 0.22, 0.41), 0.33 (95% CI: 0.26, 0.44), 0.32 (95% CI: 0.26, 0.39), and 0.37 (95% CI: 0.31, 0.44), respectively. Conclusion The prevalence of depression and anxiety among the Chinese was overall high. Monitoring and surveillance of the mental health status of the population during crises such as sudden global pandemics are imperative. Systematic review registration https://clinicaltrials.gov/, identifier [CRD42023402190].